2018
DOI: 10.1038/s41419-017-0231-0
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic inhibition of Wnt pathway suppresses osteogenic differentiation of BMSCs during osteoporosis

Abstract: Disrupted Wnt signaling in osteoblastic-lineage cells leads to bone formation defect in osteoporosis. However, the factors repressing Wnt signaling are unclear. In our study, we found that Wnt signaling was suppressed persistently in bone marrow-derived mesenchymal stem cells (BMSCs) during osteoporosis. Accordingly, histone acetylation levels on Wnt genes (Wnt1, Wnt6, Wnt10a, and Wnt10b) were declined in BMSCs from OVX mice. By screening the family of histone acetyltransferase, we identified that GCN5 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 35 publications
4
92
0
Order By: Relevance
“…Treatment of 10T1/2 cells with vulpinic acid significantly increased the mRNA level of the three Wnt genes ( Figure 2B). A recent study showed that an increase in H3 acetylation enhances the transcription of Wnt genes promoting osteogenic differentiation of bone marrow-derived MSCs [23]. As expected, our ChIP-qPCR data showed that the enrichment of acetylated H3 on the promoter region of Wnt6, 10a, and 10b was largely increased upon vulpinic acid treatment ( Figure 2C).…”
Section: Vulpinic Acid Promotes the Expression Of Wnt Genes Via H3 Acsupporting
confidence: 86%
See 2 more Smart Citations
“…Treatment of 10T1/2 cells with vulpinic acid significantly increased the mRNA level of the three Wnt genes ( Figure 2B). A recent study showed that an increase in H3 acetylation enhances the transcription of Wnt genes promoting osteogenic differentiation of bone marrow-derived MSCs [23]. As expected, our ChIP-qPCR data showed that the enrichment of acetylated H3 on the promoter region of Wnt6, 10a, and 10b was largely increased upon vulpinic acid treatment ( Figure 2C).…”
Section: Vulpinic Acid Promotes the Expression Of Wnt Genes Via H3 Acsupporting
confidence: 86%
“…transcription of Wnt genes promoting osteogenic differentiation of bone marrow-derived MSCs [23]. As expected, our ChIP-qPCR data showed that the enrichment of acetylated H3 on the promoter region of Wnt6, 10a, and 10b was largely increased upon vulpinic acid treatment ( Figure 2C).…”
Section: Vulpinic Acid Promotes the Expression Of Wnt Genes Via H3 Acsupporting
confidence: 81%
See 1 more Smart Citation
“…BMSC are osteoprogenitors, which can differentiate into matured osteoblasts. A deficiency in osteoblastogenesis from BMSC is observed to result in osteoporosis . Therefore, stimulation of proliferation and osteoblastogenesis from BMSC becomes a therapeutic strategy for osteoporosis …”
Section: Introductionmentioning
confidence: 99%
“…Further protein modification (e.g. disrupted histone acetylation) in BMSC leads to bone formation defects during osteoporosis. Pathways directly related to bone metabolism, such as osteoclast differentiation and calcium absorption, might help to determine the proteins composition in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%